Automated construction of possibilistic networks from data - Gebhardt, Jörg; Kruse, Rudolf (Zielona Góra: Uniwersytet Zielonogórski)
Possibilistic networks constitute a promising framework for efficient treatment of uncertain and imprecise information in knowledge-based systems. In this paper, we propose a new method for induction of the structure (the qualitative part) and the attached possibility distributions (the quantitative part) of a possibilistic network from a database of sample cases that may contain imprecise or missing values.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka